A high-performance PVDF-based solid electrolyte material and preparation method thereof
By optimizing the combination of PVDF matrix with electrolyte salts and conductive fillers, and introducing fibrotic structures, the nanofiber membrane is formed by electrospinning method, and combined with heat treatment technology, the problem of insufficient performance of existing PVDF-based solid electrolyte materials is solved, significantly improving the conductivity, mechanical properties and flexibility of the electrolyte membrane, and is suitable for high-performance batteries.
Patent Information
- Application Number
- CN202411835705.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-01
AI Technical Summary
The existing PVDF-based solid electrolyte materials have not yet met the requirements for improved ionic conductivity and flexibility, and it is difficult to meet the needs of modern high-performance batteries.
By optimizing the combination of PVDF matrix with electrolyte salts and conductive fillers, and introducing fibrotic structures, the nanofiber membrane is formed by electrospinning, and combined with heat treatment technology, the ionic conductivity, mechanical strength and flexibility of the electrolyte membrane are improved.
It significantly improves the ionic conductivity, mechanical strength and flexibility of the solid electrolyte membrane, and is suitable for energy storage devices such as high-performance lithium batteries, improving the energy density and service life of the battery.
Smart Images

Figure BDA0005186648740000081
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte material and a preparation method thereof, in particular to a solid electrolyte material based on a polyvinylidene fluoride (PVDF) matrix. The present invention improves the material formulation and adopts a fiberized structure forming technology to enhance the ionic conductivity, mechanical strength and flexibility of the electrolyte membrane, making the solid electrolyte material suitable for high-performance energy storage devices such as solid-state lithium batteries. Background Art
[0002] As the safety issues of traditional liquid electrolytes become increasingly prominent, solid electrolyte materials, as one of the key technologies for next-generation batteries, have been widely studied due to their good thermal stability and safety. However, although PVDF-based solid electrolytes have good chemical stability, their ionic conductivity and flexibility still need to be improved.
[0003] The present invention improves the ionic conductivity, mechanical properties and electrochemical stability of the PVDF-based solid electrolyte membrane through reasonable material ratio and optimized preparation process, especially the introduction of fibrous structure, so as to meet the needs of modern high-performance batteries. Summary of the invention
[0004] The object of the present invention is to provide a ... to solve the ... problem raised in the background technology.
[0005] The technical solution adopted by the present invention to solve the above technical problems is:
[0006] A high-performance PVDF-based solid electrolyte comprises the following components: a PVDF matrix, an electrolyte salt, a conductive filler, a plasticizer, a polymer additive and a fiberized guiding material, wherein the PVDF matrix accounts for 40-60wt%, the electrolyte salt accounts for 15-30wt%, the conductive filler accounts for 2-5wt%, the plasticizer accounts for 5-10wt%, the polymer additive accounts for 2-5wt%, and the fiberized guiding material accounts for 5-10wt%.
[0007] Preferably, the fibrosis guiding material is polylactic acid PLA or polycaprolactone PCL.
[0008] Preferably, the PVDF matrix is polyvinylidene fluoride PVDF or a modified product thereof, selected from one or more of PVDF-HFP and PVDF-co-HFP.
[0009] Preferably, the electrolyte salt is a lithium salt selected from one of LiTFSI, LiPF6 or LiFSI.
[0010] Preferably, the conductive filler is graphene, carbon nanotubes or a mixture thereof.
[0011] Preferably, the plasticizer is a polyether solvent or a carbonate solvent.
[0012] Preferably, the polymer additive is polyvinyl alcohol (PVA).
[0013] A method for preparing a high-performance PVDF-based solid electrolyte comprises the following steps:
[0014] S1, mixing the PVDF matrix or its modified product with a solvent, and stirring at a certain temperature to form a uniform solution;
[0015] S2, adding electrolyte salt to the solution obtained in the previous step, and stirring until completely dissolved;
[0016] S3, adding a conductive filler to the solution obtained in the previous step, and continuing to stir to ensure that the conductive filler is evenly dispersed;
[0017] S4, adding a polymer additive to the solution obtained in the previous step and stirring until uniform;
[0018] S5, adding the fibrosis guiding material to the solution obtained in the previous step and stirring evenly;
[0019] S6, treating the above solution by electrospinning to obtain a nanofiber membrane, wherein the electrospinning parameters include a voltage of 25 kV-30 kV, a distance between the nozzle and the collector of 15 cm-20 cm, and a solution concentration of 15-20 wt %;
[0020] S7, heat-treating the nanofiber membrane at a temperature of 150° C.-160° C. for 1-1.5 hours to remove the solvent and solidify the membrane.
[0021] Preferably, the electrospinning time in step S7 is usually 3-5 hours to ensure the formation of a uniform nanofiber membrane, and the membrane thickness is usually controlled between 70-100 μm.
[0022] Preferably, after the electrospinning in step S7, the obtained nanofiber membrane has a smooth surface and a fiber diameter of 100-150 nm.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] 1. The present invention significantly improves the ionic conductivity of the solid electrolyte membrane by optimizing the combination of PVDF matrix, electrolyte salt and conductive filler. The nanofiber structure is formed by electrospinning, which increases the specific surface area of the electrolyte membrane and promotes the migration of ions, thereby significantly improving the conductive properties of the material. The obtained electrolyte has an ionic conductivity of 1.5×10 -4 The solid electrolyte membrane of the present invention is suitable for energy storage devices such as high-performance lithium batteries and solid-state batteries, and can effectively improve the energy density and service life of the battery, meeting the application requirements of high energy density and high rate charge and discharge.
[0025] 2. The flexibility and tensile strength of the membrane are improved by adding PVA and fiberization guide materials (such as PLA, PCL). The tensile strength of the membrane can reach more than 40MPa, and it has good bendability and ductility, which is suitable for flexible batteries and other energy storage devices.
[0026] 3. Through the heat treatment process, the solvent is removed and the thermal stability of the membrane is improved. The membrane can still work stably at 180°C and is suitable for use in high temperature working environments. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0028] Embodiment 1,
[0029] A high-performance PVDF-based solid electrolyte and its preparation method:
[0030] 1. Prepare materials:
[0031] PVDF matrix: PVDF-HFP (50g)
[0032] Electrolyte salt: LiTFSI (20 g)
[0033] Conductive filler: graphene (2g)
[0034] Plasticizer: Polyvinyl alcohol (PVA) (3g)
[0035] Polymer additive: PVA (3g)
[0036] Fibrosis guiding material: polylactic acid (PLA) (5g)
[0037] Solvent: NMP (50 mL)
[0038] 2. Solution preparation: PVDF-HFP was mixed with NMP (N-methylpyrrolidone), stirred at 60°C, and stirred with a magnetic stirrer for 4 hours to ensure complete dissolution and obtain a uniform solution.
[0039] Add the electrolyte salt LiTFSI to the solution and stir until completely dissolved, ensuring that the salt is completely dissolved in the solution to avoid crystallization. Then add the conductive filler graphene and surfactant (such as PVP or Triton X-100) to promote dispersion and stir for 30 minutes. The surfactant can help the filler to disperse evenly. Add the polymer additive PVA, whose mass ratio is 5%-10% of PVDF, stir evenly, and ensure that PVA forms a uniform solution with other components in the solution. Finally, add the fiberization guide material PLA, whose mass ratio is 10%-15% of PVDF, and stir until uniform. PLA can be dissolved in NMP to form a solution with spinning properties.
[0040] 3. Electrospinning preparation:
[0041] The above solution was prepared into a nanofiber membrane by electrospinning. The electrospinning equipment was set up as follows:
[0042] Voltage: 25 kV, optimized electric field strength to ensure good fiber formation.
[0043] Solution concentration: 15 wt % (adjusted according to the viscosity of the solution and the electrospinning equipment).
[0044] The distance between the nozzle and the collector is 15 cm, which is adjusted according to the electrospinning equipment and the fluidity of the solution.
[0045] Electrospinning time: usually 4 hours, to ensure the formation of uniform nanofiber membrane, the membrane thickness is usually controlled between 80μm. The membrane thickness can be adjusted as needed.
[0046] After electrospinning, the obtained nanofiber membrane has a smooth surface, the fiber diameter is usually between 100-150nm, and has good structural stability.
[0047] 4. Heat treatment and curing:
[0048] The electrospun nanofiber membrane was placed in a heat treatment furnace for thermal curing at 150°C for 1 hour to remove the solvent and promote cross-linking of the membrane, thereby improving the structural stability of the membrane.
[0049] If necessary, a small amount of nitrogen or oxygen environment (eg, an inert gas atmosphere) may be introduced during the heat treatment to prevent excessive oxidation or thermal decomposition of the material and maintain the chemical stability of the film.
[0050] 4. Final processing:
[0051] Cooling: Cool the heat-treated film to room temperature to avoid stress cracks in the film caused by too rapid cooling.
[0052] Post-treatment: Modify the membrane surface as needed, such as coating a protective film, stretching treatment, etc., to improve the membrane's surface adhesion and mechanical properties.
[0053] Through the above steps, a solid electrolyte membrane with high ionic conductivity, high mechanical strength and high thermal stability is finally obtained, which is suitable for high-performance batteries and other energy storage devices.
[0054] Embodiment 2,
[0055] A high-performance PVDF-based solid electrolyte and its preparation method:
[0056] 1. Prepare materials:
[0057] PVDF matrix: PVDF (60g)
[0058] Electrolyte salt: LiPF 6 (18g)
[0059] Conductive filler: carbon nanotubes (2g)
[0060] Plasticizer and polymer additive: PVA (2g)
[0061] Fibrosis guide material: polycaprolactone (PCL) (6g)
[0062] Solvent: NMP (60 mL)
[0063] 2. Solution preparation: PVDF was mixed with NMP (N-methylpyrrolidone), stirred at 70°C, and stirred with a magnetic stirrer for 4 hours to ensure complete dissolution and obtain a uniform solution.
[0064] The electrolyte salt LiPF 6 Add to the solution and stir until completely dissolved, ensuring that the salt is completely dissolved in the solution to avoid crystallization. Then add the conductive filler graphene and stir for 30 minutes to ensure that the carbon nanotubes are evenly dispersed in the solution. Add PVA and stir evenly to ensure that PVA forms a uniform solution with other components in the solution. Finally, add the fiberized guide material PCL, whose mass ratio is 10%-15% of PVDF, and stir until uniform. PCL can be dissolved in NMP to form a solution with spinning properties.
[0065] 3. Electrospinning preparation:
[0066] The above solution was prepared into a nanofiber membrane by electrospinning. The electrospinning equipment was set up as follows:
[0067] Voltage: 28kV, optimized electric field strength to ensure good fiber formation.
[0068] Solution concentration: 18 wt % (adjusted according to the viscosity of the solution and the electrospinning equipment).
[0069] The distance between the nozzle and the collector was 18 cm, which was adjusted according to the electrospinning equipment and the fluidity of the solution.
[0070] Electrospinning time: usually 4 hours, to ensure the formation of uniform nanofiber membrane, the membrane thickness is usually controlled between 75μm. The membrane thickness can be adjusted as needed.
[0071] After electrospinning, the obtained nanofiber membrane has a smooth surface, the fiber diameter is usually between 100-150nm, and has good structural stability.
[0072] 4. Heat treatment and curing:
[0073] The electrospun nanofiber membrane was placed in a heat treatment furnace for thermal curing at 160°C for 1 hour to remove the solvent and promote cross-linking of the membrane, thereby improving the structural stability of the membrane.
[0074] Embodiment 3,
[0075] A high-performance PVDF-based solid electrolyte and its preparation method:
[0076] 1. Prepare materials:
[0077] PVDF matrix: PVDF-HFP (55 g)
[0078] Electrolyte salt: LiFSI (22 g)
[0079] Conductive filler: graphene (1g)
[0080] Polymer additive: PVA (4g)
[0081] Fibrosis guiding material: polylactic acid (PLA) (5g)
[0082] Solvent: NMP (55 mL)
[0083] 2. Solution preparation: PVDF was mixed with NMP (N-methylpyrrolidone), stirred at 60°C, and stirred with a magnetic stirrer for 4 hours to ensure complete dissolution and obtain a uniform solution.
[0084] Add the electrolyte salt LiFSI to the solution and stir until completely dissolved, ensuring that the salt is completely dissolved in the solution to avoid crystallization. Then add the conductive filler graphene and stir for 1 hour to ensure that the graphene is evenly dispersed in the solution. Add PVA and stir evenly to ensure that PVA forms a uniform solution with other components in the solution. Finally, add the fiberizing guide material PLA, with a mass ratio of 10%-15% of PVDF, and stir until uniform. PLA can be dissolved in NMP to form a solution with spinning properties.
[0085] 3. Electrospinning preparation:
[0086] The above solution was prepared into a nanofiber membrane by electrospinning. The electrospinning equipment was set up as follows:
[0087] Voltage: 27 kV, optimized electric field strength to ensure good fiber formation.
[0088] Solution concentration: 16 wt % (adjusted according to the viscosity of the solution and the electrospinning equipment).
[0089] The distance between the nozzle and the collector is 15 cm, which is adjusted according to the electrospinning equipment and the fluidity of the solution.
[0090] Electrospinning time: usually 4 hours, to ensure the formation of uniform nanofiber membrane, the membrane thickness is usually controlled between 85μm. The membrane thickness can be adjusted as needed.
[0091] After electrospinning, the obtained nanofiber membrane has a smooth surface, the fiber diameter is usually between 120-160nm, and has good structural stability.
[0092] 4. Heat treatment and curing:
[0093] The electrospun nanofiber membrane was placed in a heat treatment furnace for thermal curing at a temperature of 155°C for 1.5 hours to remove the solvent and promote cross-linking of the membrane, thereby improving the structural stability of the membrane.
[0094] Comparative experiment: Comparison between traditional electrolyte membrane and solid electrolyte membrane of the present invention
[0095]
[0096] Ionic conductivity: The solid electrolyte membrane of the present invention is superior to the traditional PVDF membrane and the liquid electrolyte membrane in ionic conductivity, especially Example 2, which has a higher conductivity and meets the high efficiency requirements of modern batteries.
[0097] Tensile strength: The tensile strength of the embodiment is significantly higher than that of the traditional PVDF electrolyte membrane, showing strong mechanical properties and being able to meet the needs of high-power and high-rate applications.
[0098] Membrane thickness: The membrane thickness of the embodiment is thinner, which helps to reduce the internal resistance of the battery and improve the energy density.
[0099] Ion migration number: The ion migration number of the membrane of the present invention is relatively high, especially Example 2 (0.6), which can provide more efficient lithium ion conduction.
[0100] Thermal stability: The thermal stability of the membrane of the present invention is better than that of traditional materials, suitable for a wider temperature range, and increases the application reliability of the battery.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-performance PVDF-based solid electrolyte, characterized in that: The invention comprises the following components: PVDF matrix, electrolyte salt, conductive filler, plasticizer, polymer additive and fiberized guiding material, wherein the PVDF matrix accounts for 40-60wt%, the electrolyte salt accounts for 15-30wt%, the conductive filler accounts for 2-5wt%, the plasticizer accounts for 5-10wt%, the polymer additive accounts for 2-5wt% and the fiberized guiding material accounts for 5-10wt%.
2. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The fibrosis guiding material is polylactic acid PLA or polycaprolactone PCL.
3. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The PVDF matrix is polyvinylidene fluoride PVDF or a modified product thereof, selected from one or more of PVDF-HFP and PVDF-co-HFP.
4. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The electrolyte salt is a lithium salt selected from one of LiTFSI, LiPF6 or LiFSI.
5. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The conductive filler is graphene, carbon nanotube or a mixture thereof.
6. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The plasticizer is a polyether solvent or a carbonate solvent.
7. A high-performance PVDF-based solid electrolyte according to claim 1, characterized in that: The polymer additive is polyvinyl alcohol (PVA).
8. A method for preparing the high-performance PVDF-based solid electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing the PVDF matrix or its modified product with a solvent, and stirring at a certain temperature to form a uniform solution; S2, adding electrolyte salt to the solution obtained in the previous step, and stirring until completely dissolved; S3, adding a conductive filler to the solution obtained in the previous step, and continuing to stir to ensure that the conductive filler is evenly dispersed; S4, adding a polymer additive to the solution obtained in the previous step and stirring until uniform; S5, adding the fibrosis guiding material to the solution obtained in the previous step and stirring evenly; S6, treating the above solution by electrospinning to obtain a nanofiber membrane, wherein the electrospinning parameters include a voltage of 25 kV-30 kV, a distance between the nozzle and the collector of 15 cm-20 cm, and a solution concentration of 15-20 wt %; S7, heat-treating the nanofiber membrane at a temperature of 150° C.-160° C. for 1-1.5 hours to remove the solvent and solidify the membrane.
9. The method for preparing a high-performance PVDF-based solid electrolyte according to claim 8, characterized in that: The electrospinning time in step S7 is usually 3-5 hours to ensure the formation of a uniform nanofiber membrane, and the membrane thickness is usually controlled between 70-100 μm.
10. The method for preparing a high-performance PVDF-based solid electrolyte according to claim 9, characterized in that: After the electrospinning in step S7, the obtained nanofiber membrane has a smooth surface and a fiber diameter of 100-150 nm.